2019
DOI: 10.1016/j.asr.2019.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Galileo data on the solutions of the variometric approach for displacement analysis

Abstract: The Variometric Approach for Displacement Analysis Standalone Engine (VADASE) was successfully applied for seismological and monitoring purposes using GPS observations. In this work, GPS inter-operable and specific signals transmitted by Galileo satellites were considered to evaluate the impact of Galileo observations on VADASE solutions. The repetition period of the Galileo constellation was investigated to identify the time-windows with the most abundant number of Galileo satellites. Observation packages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…For instance, Geng et al examined the VA performance with GPS and GPS + BeiDou observations at a 5 Hz sampling rate to determine large displacements caused by a mega-earthquake, and they reported that the combination of GPS and BeiDou detected seismic waveforms of about 20% better than the single system [15]. Tesolin et al conducted a zero-displacement experiment to examine the contribution of Galileo observations at a 1 Hz sampling rate to the VA technique, and they stated that GPS + Galileo observations are better than single-system solutions [16]. Zang et al employed GPS, GLONASS, and BeiDou observations at a 1 Hz sampling rate to evaluate the ability of the VA method in earthquake magnitude estimation, and they reported that multi-GNSS observations provide more reliable displacement compared to a single system [17].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Geng et al examined the VA performance with GPS and GPS + BeiDou observations at a 5 Hz sampling rate to determine large displacements caused by a mega-earthquake, and they reported that the combination of GPS and BeiDou detected seismic waveforms of about 20% better than the single system [15]. Tesolin et al conducted a zero-displacement experiment to examine the contribution of Galileo observations at a 1 Hz sampling rate to the VA technique, and they stated that GPS + Galileo observations are better than single-system solutions [16]. Zang et al employed GPS, GLONASS, and BeiDou observations at a 1 Hz sampling rate to evaluate the ability of the VA method in earthquake magnitude estimation, and they reported that multi-GNSS observations provide more reliable displacement compared to a single system [17].…”
Section: Introductionmentioning
confidence: 99%